Sinterability and conductivity of barium doped aluminium lanthanum oxyapatite La9.5Ba0.5Si5.5Al0.5O26.5 electrolyte of solid oxide fuel cells - Cao, X.; Jiang, San Ping (Elsevier B.V., 2012)
Apatite ceramics are interesting alternative solid oxide fuel cells (SOFCs) electrolytes because of their open structure for the transportation of oxide ions and their good chemical stability. This study reports the influence of barium doping on the microstructure, sinterability and oxide conductivity properties of the aluminium lanthanum oxyapatite La9.5Ba0.5Si5.5Al0.5O26.5. SEM results show that lanthanum substitution with barium improves the sinterability of apatite ceramics. The barium doping also enhances the conductivity of the aluminium lanthanum silicates. The oxygen ion conductivity of La9.5Ba0.5Si5.5Al0.5O26.5 sintered at 1600°C is 2.21 × 10−2 S cm−1 at 800°C, higher than 9.81 × 10−3 S cm−1 of La10Si5AlO26.5 sample prepared under the same conditions. The results in the present study demonstrate that doping Ba on the La site for aluminium lanthanum oxyapatite reduces the sintering temperature and improves the ion conductivity. The enhancement of Ba dopant is mainly on the improvement of the densification and thus substantially reduced grain boundary resistance of aluminium lanthanum oxyapatite particularly at low temperatures.